Assessment of the Impact of Assisted Reproductive Technology on the Incidence of Vacuum-Assisted Delivery - Ryosuke Arakaki; Wataru Isono; Hiroaki Fukuda; Junya Tanaka; Arisa Minamino; Shiko Hayash (Clinical and Experimental Obstetrics & Gynecology)
Background: In Japan, the rising number of nulliparous women of advanced maternal age (AMA) conceiving via assisted reproductive technology (ART) is anticipated to lead to an increase in adverse labor outcomes, even when the progression of labor appears to be favorable. Therefore, by examining the likelihood of vacuum-assisted delivery (VaD), our aim was to confirm the potential adverse impact of AMA and a history of ART treatment on labor outcomes. Methods: In this retrospective cohort study, the medical records of 542 nulliparous pregnant women aged 30 years or older who delivered at our hospital between April 1, 2017 and March 31, 2024, were reviewed with the approval of the institutional review board. First, we compared the characteristics, including labor conditions and delivery outcomes, of 417 patients who underwent spontaneous vaginal delivery (SVD) with those of 125 patients who underwent VaD. Next, we performed multivariate analysis to assess the effect of various representative factor, including AMA and a history of ART treatment, in order to confirm their actual impact on the likelihood of VaD. Results: In the simple comparison, maternal age, history of ART treatment, the amount of blood loss, and Apgar scores differed significantly between the two groups. However, in the multivariate analysis, only two factors, including history of ART treatment and uterine leiomyoma status, were found to significantly affect the likelihood of VaD. Conclusions: We detected a clear effect of both uterine leiomyoma status and a history of ART treatment on the likelihood of VaD, while AMA did not emerge as a significant factor. Further studies are needed to confirm the adverse impact of a history of ART treatment on labor progression.